Rancangan Pengembangan Aplikasi Dokumentasi Clinical Pathway Berbasis Web - Adi Sadli (Universitas Bandar Lampung (UBL), 2021)
Clinical Pathway is a procedural model or service flow from a hospital to carry out clinical actions, usually starting from patient registration to patient discharge. The most important thing in implementing this Clinical Pathway is as a control function for the quality of hospital services. In practice, most of the procedural implementation is still done manually, meaning that it has not used a computerized system. Usually, Clinical Pathways are written in the form of a form with action instructions on one side, and service time on the other. The amount of service time is converted into days based on clinical instructions, but this can also differ depending on the development of the disease or existing actions, for example, Clinical Pathways for chronic diseases may have a number of weeks or months. The Clinical Pathway documentation application that will be designed is a web-based application that will be able to utilize the hospital's intranet/internet connection in its operation. This application is expected to be used as an answer to the need for faster, more effective, and measurable Clinical Pathways implementation. In its design, this application will continue to use the concept of procedural stages as done manually (according to Standard Operating Procedures) which has been carried out by the hospital, only the application is already in a computerized system where every aspect of the User will be connected to each other. For the design stage, this application itself is only intended for certain diseases such as Ischemic Stroke or depending on the needs of the Hospital. The implementation for this application is still being carried out on a trial basis, the aim is to obtain temporary data on how to see the impact of using this application on the level of service of the hospital that will be the executor of the trial of this application.